Twisted amide electrophiles enable cyclic peptide sequencing. Issue 27 (16th June 2015) - Zaretsky, Serge; Rai, Vishal; Gish, Gerald; Forbes, Matthew W.; Kofler, Michael; Yu, Joy C. Y.; Tan, Joanne; Hickey, Jennifer L.; Pawson, Tony; Yudin, Andrei K.
Abstract : Preserving the electrophilic carbonyl group of an aziridine amide in a macrocycle enables cyclic peptide sequencing by chemoselective linearization and tandem mass spectrometry. Abstract : There is an ever-increasing interest in synthetic methods that not only enable peptide macrocyclization, but also facilitate downstream application of the synthesized molecules. We have found that aziridine amides are stereoelectronically attenuated in a macrocyclic environment such that non-specific interactions with biological nucleophiles are reduced or even shut down. The electrophilic reactivity, revealed at high pH, enables peptide sequencing by mass spectrometry, which will further broaden the utility of aziridine amide-containing libraries of macrocycles.